Dokumenty życia społecznego odbiciem rzeczywistości i zapisem historii - Ludorowski, Leszek (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2005)
[Documents of Social Life as Reflection of Reality and as Historical Record] The author of the article explains the term “documents of social life” against the background of its equivalents functioning in other countries, and he demonstrates its ambiguity. In the practical dimension, that results in different classification of library documents in various libraries, and considering them documents of social life. The author broadly explains the abovementioned term, discussing the expert Polish literature from the recent decades, which provides an opportunity for many comparisons. He also points out the significance of collect-ing such literature in the light of the experience of other countries, and also in the context of the existing term of “grey literature”. The article makes use of several studies, often extricating from them interesting points of view and opinions about the peculiar cultural phenomenon of fugitive documents.